PENANGANAN LANJUT USIA DI POSYANDU DESA MUARA LEMBU KECAMATAN SINGINGI KABAUPATEN KUANTAN SINGINGI - Azizah Azizah; Titi Maemunaty; Wilson Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study is about the treatment of the elderly in the posyandu, Muara Lembu Village, Singingi District, Kuantan Singing District. (1) Health Services, (2) Food and Nutrition Services, (3) Morning Gymnastics Services. The purpose of this study was to determine the elderly in the Posyandu, Muara Lembu Village, Singingi District, Kuantan Singingi Regency. Elderly is a term for individuals who have entered the period of late adulthood or old age, where the period of late adulthood or old age is a closing period for the vulnerable lives of elderly people. Therefore, Posyandu was held for the elderly and also handling for the elderly who were in the Posyandu. The older a person gets, the more susceptible he is to a disease due to a decrease in his body system. The elderly tend to experience a decrease in the musculoskeletal system. This decrease in the musculoskeletal system can affect physical mobility in the elderly and can even result in impaired physical mobility in the elderly. Handling the elderly is a way of providing social welfare services for the elderly through health adjustments by filling free time in the form of useful activities in creating a relationship that is appropriate with fellow elderly, as follows: 1) Health services for the elderly 2) Food and nutrition services elderly 3) Gymnastics services for the elderly. The results of this study will be explained about research findings about understanding the handling of the elderly in the posyandu, Muara Lembu village, Singingi district, Kuantan Singing district.Key Words: Handling, Service, Posyandu.